Acid leaching recovery and occurrence modes of rare earth elements (REEs) from natural kaolinites. (1st January 2022) - Ji, Bin; Li, Qi; Honaker, Rick; Zhang, Wencai
Highlights: Around 10% and 56% of total REEs were extracted from two natural kaolinite samples. The recovery of REEs increased significantly after calcination at 500–900 °C. Mineralogical changes of kaolinite agreed with the variations in the leaching recovery of REEs. Leaching characteristics of REEs were different from that of constituent elements of kaolinite. A portion of the REEs occurred as rare earth-bearing minerals physically associated with kaolinite. Abstract: Leaching recovery of rare earth elements (REEs) from two natural kaolinite samples were investigated in this study. Using standard leach conditions without pretreatment, only 10% and 56% of the total REEs were leached from the raw samples, respectively. However, pretreatment by calcination at temperatures between 500 °C and 900 °C increased the leaching recovery of total REEs to values as high as 93% for both samples. Mineralogical characterization and acid leaching results suggested that the decomposition of the kaolinite structure occurs as a function of calcination temperature. Comparisons between the REEs and the major constituent elements of kaolinite showed that their leaching characteristics contrasted. Moreover, sequential chemical extraction results suggested that the fractions of REEs occurring in an ion-adsorption form were negligible. Therefore, the REEs were primarily associated with REE-bearing minerals of which, a portion was encapsulated in kaolinite aggregates while the remaining existed as liberated particles. These association characteristics were proven through SEM-EDX analysis. Based on the mineralogy characterization, acid leaching, and sequential chemical extraction results, it was concluded that the REEs have complicated modes of occurrence and association characteristics with kaolinite. The positive impacts of calcination on the leaching recovery of REEs are likely due to two mechanisms, i.e., (1) liberation of the encapsulated REE-bearing minerals through expansion of the kaolinite aggregates, and (2) conversion of the REE-bearing minerals into more soluble forms.